International Conference on Acoustics, Speech, and Signal Processing
DOI: 10.1109/icassp.1989.266448
|View full text |Cite
|
Sign up to set email alerts
|

Phoneme segmentation using spectrogram reading knowledge

Abstract: This paper presents a method for, a n d performance of, p h o n e m e s e g m e n t a t i o n b y a n e x p e r t s y s t e m u t i l i z i n g spectrogram reading strategy a n d knowledge. T h e e x p e r t system detects phonemes i n a spectrogram a n d determines their b o u n d a r i e s as well as their c o a r s e categories. T o simulate a human expert spectrogram reading process, the system performs assumption-based inference with certainty factors, a n d top-down acoustic f e a t u r e extraction u n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…S PECTROGRAMS, as time-frequency representations of audio signals, have been used as input for neural network models since the 1980s [1][2][3]. Different types of spectrograms are tailored to different applications.…”
Section: Introductionmentioning
confidence: 99%
“…S PECTROGRAMS, as time-frequency representations of audio signals, have been used as input for neural network models since the 1980s [1][2][3]. Different types of spectrograms are tailored to different applications.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that FFT spectrogram was found to be a more robust feature for segmentation and classification even in noisy environments [7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The spectrum of the signal is shown in every small vertical slice of the spectrogram. The robustness and convenience of the spectrogram in speech application is approved through reading (Laprie and Berger, 1996;Hatazaki et al, 1989;Silverman and Lee, 1987;Hunt, 1987;Connolly and Edmonds, 1986;Zue and Lamel, 1986;Zue and Cole, 1979;Mporas et al, 2007).…”
Section: Introductionmentioning
confidence: 99%